Analyzing the degradation of roadside infrastructure - Augustine, Luke Strand (Kansas State University, 2019)
Metals are used in a variety of different ways to strengthen and enhance transportation infrastructure. Steel, one of the most commonly used metals, can be found as strips in MSE walls and corrugated metal pipes running underneath roads and highways. These elements are often galvanized or coated with another material in an effort to protect and increase the service life. Having the ability to assess the present state of metals in infrastructure is important when projecting rehabilitation or replacement. The objectives of this research were twofold. The first was to observe the current state of corrugated metal pipe in Kansas. This work was done as a follow up to two previous studies conducted by the Kansas Department of Transportation that examined the effects of a policy change in 1975 that allowed for lighter gauge corrugated metal pipe to be used in their projects. The results from these studies were compared with those found in this research and were consistent with the conclusion that the policy change led to a shorter service life expectancy for pipes installed after 1975. A reversion to pre-1975 policy corrected that problem, validated by the current study. Additional characteristics investigated with regards to the deterioration rate of the corrugated metal pipes included material type, corrugation dimensions, resistivity, and chloride concentration in the surrounding soil. The second objective was to evaluate the corrosive environments of aggregate backfill in MSE walls. This work was done as an exploration of a unique application of electrical resistivity where measurements were taken into a vertical plane (into the backfill of a mechanically stabilized earth wall directly behind the panels of the wall) instead of a horizontal plane (typically the ground). Five mechanically stabilized earth walls in total were analyzed by taking into-the-wall measurements at the base. Three walls were selected to take electrical resistivity surveys at the top of the wall and the backfill of four walls was classified. These results support the potential of using a modified four-electrode electrical resistivity measurement to identify corrosive environments in MSE walls.
Keywords: Corrosion; Mechanically stabilized earth wall; Corrugated metal pipe